‘Iddah Perempuan Kematian Suami : (Analisis Hadis-Hadis Tentang ‘Iddah Karena Kematian Suami) - Hanafiyah, Mahmudi (Ameena Journal, 2024)
Death is an event felt by every living creature. Not only is it an event that is feared by the person who befell it, death is also a very difficult thing for the person left behind, including a woman whose husband died. Women who are undergoing a period of mourning for the death of their husband need to heed several taboos during the 'iddah period. Nowadays, this is often overlooked by some women with various factors causing it. In this article, the author wants to examine the 'iddah of women whose husbands die from a hadith perspective by formulating the problem of the nature of 'iddah and what provisions and things must be fulfilled for women who are undergoing the 'iddah period. This research is library research with a qualitative research type and a normative approach. The results of the study concluded two things. Firstly, what is meant by 'iddah is the tough period for a wife who separates from her husband for the sole purpose of ta'abbud, or because of anxiety over the death of her husband, or to find out whether her womb is empty or not so that she can marry another man and look after her offspring. Second, women whose husbands died during the 'iddah discussion were classified into two groups, namely pregnant or not pregnant. A pregnant woman will end her 'iddah period by simply giving birth, whether she is free or a slave, if the child she is carrying is her husband's child. Meanwhile, a woman who is not pregnant will end her 'iddah period after four months and ten days, if she is free, or a slave with the status of ummu walad. As for servants who are not ummu walad, their 'iddah is half that of a free person's 'iddah, namely two months and five days. A woman whose husband dies must be provided with a place to live, based on strong opinions from two different opinions, and she cannot leave the house before the end of the 'iddah period, unless there is a need. They are also obliged to observe ihdad during the 'iddah period.